ANALISIS GAYA BAHASA PERSONIFIKASI DALAM KUMPULAN SYAIR LAGU EBIET G. ADE - Syifa Deviyola; Erlina Zahar; Uli Wahyuni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is aimed at describing personification in the collection of song rhymes by Ebiet G. Ade. This research is descriptive qualitative. Descriptively, this research describes the features of personification in the collection of song rhymes by Ebiet G. Ade. The data is written form in the form of sentence which has personification in the collection of song rhymes by Ebiet G. Ade. Based on the result, it can be concluded that there are 47 quotes in the personification in the collection of song rhymes by Ebiet G. Ade. By identifying the meaning of the rhymes in Ebiet G. Ade songs, readers or listeners can understand messages that are delivered by the composer. The meaning of personification in the collection of song rhymes represent humans life, nature life, religious life, society life, politics and affection life. Key Words: personification, meaning, rhyme